Classrooms as ‘safe houses’? The ethical and emotional implications of digital storytelling in a university writing classroom - Stewart, Kristian D (Critical Studies in Teaching and Learning, 2023)
This  paper  reports  the  findings  of  a  digital  storytelling  praxis  within  a  higher  education classroom  located  outside  of  Metro  Detroit  in  the  United  States.  Drawing  on Zembylas’s (2006,  2008)  scholarship  on  emotion  in  the  production  of  knowledge  and  the  teacher’s  role, adjacent   to   literature   surrounding   personal   writing   and   safe   houses   for   learning,   an investigation  of  student  perceptions  of  digital  storytelling  within  a  writing  classroom  took place during the 2016and 2017 academic years. Data highlights the students’ interest for the emotionally-driven course content digital storytelling encourages, as it taught students how to insert genre conventions into their own writing. Digital storytelling, according to the students, also supplied a means for students to develop relationships with their peers as many students felt isolated on this largely commuter campus. Students additionally viewed the curriculum as promoting ‘real world’ skills they could transfer outside of the classroom and into their lives. However,  to  craft  digital  stories,  data  revealed  how  students  turned  toward  sharing  personal (and or traumatic) narratives. This can be problematic in terms of emotional safety if students are made to feel they must leverage emotions for grades and are then forced to broadcast their digital stories in a public forum. To lessen these concerns, strategies for implementing digital storytelling  into  the  curriculum  are  provided.  Lastly,  the  author  concludes  that  educating students  within  a  Trump  presidency  requires  a  different  pedagogical  approach.  Assignments such  as digital  storytelling that  merge  the  scholarly  and  the  personal,  alongside  nurturing empathy, open dialogue, and building relationships might offer a direction forward.